Low dose cone beam CT for paediatric image-guided radiotherapy: Image quality and practical recommendations. (October 2021) - Bryce-Atkinson, Abigail; De Jong, Rianne; Marchant, Tom; Whitfield, Gillian; Aznar, Marianne C.; Bel, Arjan; van Herk, Marcel
Highlights: Anatomical noise is the dominant source of image noise in paediatric CBCT. CNR between fat and muscle was maintained in over 90% of cases for doses ≥1 mGy. Increasing dose above 1 mGy does not improve image quality or registration accuracy. Low dose paediatric CBCT protocols are recommended based on the imaging need. Abstract: Purpose: Cone beam CT (CBCT) is used in paediatric image-guided radiotherapy (IGRT) for patient setup and internal anatomy assessment. Adult CBCT protocols lead to excessive doses in children, increasing the risk of radiation-induced malignancies. Reducing imaging dose increases quantum noise, degrading image quality. Patient CBCTs also include 'anatomical noise' (e.g. motion artefacts), further degrading quality. We determine noise contributions in paediatric CBCT, recommending practical imaging protocols and thresholds above which increasing dose yields no improvement in image quality. Methods and materials: Sixty CBCTs including the thorax or abdomen/pelvis from 7 paediatric patients (aged 6–13 years) were acquired at a range of doses and used to simulate lower dose scans, totalling 192 scans (0.5–12.8 mGy). Noise measured in corresponding regions of each patient and a 10-year-old phantom were compared, modelling total (including anatomical) noise, and quantum noise contributions as a function of dose. Contrast-to-noise ratio (CNR) was measured between fat/muscle. Soft tissue registration was performed on the kidneys, comparing accuracy to the highest dose scans. Results: Quantum noise contributed <20% to total noise in all cases, suggesting anatomical noise is the largest determinant of image quality in the abdominal/pelvic region. CNR exceeded 3 in over 90% of cases ≥ 1 mGy, and 57% of cases at 0.5 mGy. Soft tissue registration was accurate for doses > 1 mGy. Conclusion: Anatomical noise dominates quantum noise in paediatric CBCT. Appropriate soft tissue contrast and registration accuracy can be achieved for doses as low as 1 mGy. Increasing dose above 1 mGy holds no benefit in improving image quality or registration accuracy due to the presence of anatomical noise.